The Influence of Motivation and Work Discipline on Teacher Performance in Public Elementary Schools in Barumun Selatan Subdistrict, Padang Lawas Regency - Surlan; Ali Mukti Tanjung; Ida Zulfida (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Teacher performance is essentially the ability of teachers to transfer knowledge and societal values to students through the learning process. Teacher performance is reflected in how teachers plan, implement, and assess the teaching and learning process, which is influenced by their work ethic and professional discipline in the learning process. The research method used is quantitative with a correlation descriptive approach. Data collection was done using a questionnaire. The results show that motivation significantly affects teacher performance in public elementary schools in the Barumun Selatan Subdistrict, Padang Lawas Regency, with a t-value for the motivation variable of 6.855 > 1.035 and a significance level of 0.000 < 0.05, and a correlation coefficient of 0.545 (54.50%). The better the work motivation, the higher the teacher performance will be. Work discipline also significantly affects teacher performance in public elementary schools in Barumun Selatan Subdistrict, with a t-value for the work discipline variable of 5.236 > 1.989 and a significance level of 0.000 < 0.05, with a correlation coefficient of 0.417 (41.70%). The higher the work discipline, the better the teacher performance will be. Motivation and work discipline, simultaneously, have a significant influence on teacher performance in public elementary schools in Barumun Selatan Subdistrict, with an F-value of 262.625 > the F-table value of 3.105. 85.90% of the variation in teacher performance can be explained by motivation and work discipline together, while the remaining 14.10% is explained by other factors, such as personality competence and social competence variables.